Pengaruh Pendidikan Kesehatan Menggunakan Media Video Animasi Terhadap Pengetahuan dan Keterampilan Pemeriksaan Payudara Sendiri Pada Remaja Putri - Yanti Cahyati; Erna Rosanti; Sofia Februanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2024)
Background: Adolescence lasts from the age of 10-19 years who have experienced the formation of puberty hormones so that they have an increased risk of developing breast cancer. Breast cancer can be detected by breast self-examination (BSE). However, there are still many adolescents who do not know how to do it, so health education is needed, one of which is through animated videos Purpose: To impact of health education using animated video media on the knowledge and skills of BSE in adolescent girls Methods: This study used a Quasi-Experimental design with a pretest-posttest with a control design. To measure SADARI knowledge and skills using the instrument of the SADARI knowledge questionnaire sheet and the SADARI skill observation sheet. The sample was taken using proportional stratified sampling of 19 respondents for each intervention group and control group. Education about BSE was provided to the intervention group through animated videos and control groups through leaflet media. Statistical analysis was performed using a dependent t-test and an independent t-test with an alpha value of 0.05 Result: There was a significant difference in the average score of knowledge and skills before education in the intervention group using animated video media 57.85 and 47.31 to 79.73 and 73.82 (p-value 0.000 < α 0.05), while for the control group using leaflet media before education 47.31 and 19.17 to 62.31 and 66.95 (p-value 0.000). There was a significant difference in average post-education scores between the two groups with a p-value of 0.000 for knowledge and a p-value of 0.003 for skills Implication: There is an effect of health education using animated video media on adolescent girls' knowledge and skills about self-awareness